A synthesis of alternative testing procedures for event studies* - CHANDRA, RAMESH; BALACHANDRAN, BALA V. (Contemporary Accounting Research, 1990)
The alternative versions of the t ‐test found in event studies result from different weighting schemes for abnormal returns, different abnormal return models, and different correlational structures among abnormal returns. In the presence of dependencies among abnormal returns, the generalized least squares t ‐tests are much more sensitive to the mis‐specifications in the abnormal return model than are the nongeneralized t ‐tests. Therefore, when analyzing contemporaneous returns, particularly with samples exhibiting a large industry concentration, a nongeneralized t ‐test should be preferred to a generalized least squares t ‐test because of the dependencies that may exist. Because the generalized least squares t ‐tests are highly sensitive to errors in specifying an appropriate abnormal return model, a portfolio time‐series ordinary least squares regression should be preferred to a generalized least squares regression even when the variance or covariance matrix of abnormal returns can be estimated with a high degree of reliability. In testing for the mean effects, the concern for event period variance increases seems to be unwarranted, and the variance estimators using event period data are inefficient and biased. The issue is not whether variance increases in an event period, but which variance is to be used: that of the event period or of the nonevent period? Answers to such questions are presented in this paper. Résumé. Les différentes versions possibles du test t que l'on trouve dans les études d'événements résultent de différents systèmes de pondération des rendements anormaux, de différents modèles de rendements anormaux et de différentes structures de corrélation des rendements anormaux. Lorsqu'il existe une dépendance entre les rendements anormaux, les tests t généralisés des moindres carrés sont beaucoup plus sensibles aux défauts de construction du modèle des rendements anormaux que ne le sont les tests t non généralisés. C'est pourquoi lorsqu'on analyse des rendements simultanés, en particulier si l'échantillon présente une forte concentration industrielle, le test t non généralisé est préférable au test t généralisé des moindres carrés, compte tenu des dépendances qui peuvent exister. Les tests t généralisés des moindres carrés étant très sensibles aux défauts de construction du modèle approprié de rendements anormaux, l'application de la méthode classique des moindres carrés à une série chronologique relative à un portefeuille est préférable à la régression généralisée des moindres carrés, même s'il est possible d'estimer avec un degré élevé de fiabilité la matrice de variance ou de covariance des rendements anormaux. Dans le test des effets moyens, la préoccupation relative aux augmentations de la variance de la période d'événements semble être injustifiée, et les estimateurs de la variance fondés sur les données de la période d'événements sont inefficients et biaisés. Il ne s'agit pas de déterminer si la variance augmente pendant la période d'événements, mais quelle variance doit être utilisée: celle de la période d'événements ou une autre. Les auteurs répondent à ces questions.